2009
DOI: 10.1128/iai.00950-08
|View full text |Cite
|
Sign up to set email alerts
|

TheYersinia pestis caf1M1A1Fimbrial Capsule Operon Promotes Transmission by Flea Bite in a Mouse Model of Bubonic Plague

Abstract: Plague is a zoonosis transmitted by fleas and caused by the gram-negative bacterium Yersinia pestis. During infection, the plasmidic caf1M1A1 operon that encodes the Y. pestis F1 protein capsule is highly expressed, and anti-F1 antibodies are protective. Surprisingly, the capsule is not required for virulence after injection of cultured bacteria, even though it is an antiphagocytic factor and capsule-deficient Y. pestis strains are rarely isolated. We found that a caf-negative Y. pestis mutant was not impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 67 publications
4
71
3
1
Order By: Relevance
“…For instance, the ymt gene located on the pFra plasmid encodes phospholipase D, which enhances the ability of Y. pestis to colonize the flea midgut (Hinnebusch et al 2002). The pFra plasmid also carries the caf1M1A1 operon, which encodes a protein capsule that is required for infection of mice by the flea-borne route (Sebbane et al 2009). The pla gene carried on the pPst plasmid encodes a plasminogen activator that is specifically required for inducing the bubonic form of plague in the mouse after a flea bite (Sebbane et al 2006).…”
Section: Lateral Gene Transfermentioning
confidence: 99%
“…For instance, the ymt gene located on the pFra plasmid encodes phospholipase D, which enhances the ability of Y. pestis to colonize the flea midgut (Hinnebusch et al 2002). The pFra plasmid also carries the caf1M1A1 operon, which encodes a protein capsule that is required for infection of mice by the flea-borne route (Sebbane et al 2009). The pla gene carried on the pPst plasmid encodes a plasminogen activator that is specifically required for inducing the bubonic form of plague in the mouse after a flea bite (Sebbane et al 2006).…”
Section: Lateral Gene Transfermentioning
confidence: 99%
“…Sebbane and colleagues 50 reported that F1 pili contribute to the transmission of plague via flea bite; however, F1 is not essential for bubonic or pneumonic plague in mice. 20 Herein, we report that F1 variants, engineered or naturally acquired, are less likely to cause bubonic plague after s.c. injection into guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Caf1 capsule is strongly influenced by temperature, where essentially no capsule is identified in the flea vector or at temperatures <35°C [54]. The caf1 gene is the most highly expressed genes during infection of the mammal, indicating that it is a virulence factor [54].…”
Section: The Capsular Antigen Fraction 1 (Caf1) Capsulementioning
confidence: 99%
“…The Caf1 capsule is made up of the Fraction 1 (F1) antigen, a fimbrial protein that accrues on the bacterial surface to form a capsule unique to Y. pestis [54].…”
Section: The Capsular Antigen Fraction 1 (Caf1) Capsulementioning
confidence: 99%
See 1 more Smart Citation